2022
DOI: 10.1016/j.jceh.2021.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Non-alcoholic Fatty Liver Disease in India: A Systematic Review and Meta-analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 59 publications
(39 reference statements)
2
17
3
Order By: Relevance
“…Notably, the high-risk group had a higher prevalence of NAFLD at 52.8%, comparable to our estimate of 55.1% [28]. Conversely, those in the average-risk group were noted to have a lower prevalence of NAFLD at 28.2% compared to our estimate of 25.2% [28]. Despite the significant heterogeneity among studies and sampling bias, the above findings of the Indian analysis reflect similarly in our study, which found a significant association between NAFLD and metabolic syndrome, general obesity, central obesity, diabetes, dysglycaemia, dyslipidaemia and hypertension.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Notably, the high-risk group had a higher prevalence of NAFLD at 52.8%, comparable to our estimate of 55.1% [28]. Conversely, those in the average-risk group were noted to have a lower prevalence of NAFLD at 28.2% compared to our estimate of 25.2% [28]. Despite the significant heterogeneity among studies and sampling bias, the above findings of the Indian analysis reflect similarly in our study, which found a significant association between NAFLD and metabolic syndrome, general obesity, central obesity, diabetes, dysglycaemia, dyslipidaemia and hypertension.…”
Section: Discussionsupporting
confidence: 88%
“…The high-risk group consisted of obesity, overweight, pre-diabetes, diabetes mellitus, coronary artery disease, metabolic syndrome, obstructive sleep apnoea, polycystic ovarian syndrome and elevated liver enzymes. Notably, the high-risk group had a higher prevalence of NAFLD at 52.8%, comparable to our estimate of 55.1% [28]. Conversely, those in the average-risk group were noted to have a lower prevalence of NAFLD at 28.2% compared to our estimate of 25.2% [28].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A recent meta-analysis from India reported the estimated pooled prevalence to be 38.6% in adults and alarmingly 35.4% in children. 22 As reported by Draijer et al, only one-third of children with pediatric NAFLD have a resolution of steatosis as adults, while 6% develop NAFLD-related fibrosis. 23 These two results highlight the need for increased inclusivity and representation of a South East Asian cohort in studies pertaining to NAFLD.…”
mentioning
confidence: 88%
“…The global prevalences of NAFLD and NASH are estimated to be 25% and 1.5% -6.5%, respectively. In India, 38.6% adults and 35.4% children have been found to suffer from NAFLD [6].…”
Section: Introductionmentioning
confidence: 99%